Peran Pola Asuh Orang Tua dalam Meningkatkan Kesejahteraan Sosial Anak ADHD - Refyna Nurwanti Kurniawan; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the role of parenting styles in improving the social well-being of children with Attention Deficit Hyperactivity Disorder (ADHD). Children with ADHD often experience difficulties in social interaction, characterized by impulsive behavior, hyperactivity, and low attention control, which affect their ability to adapt to social environments. This research employed a qualitative approach with a descriptive method to gain an in-depth understanding of parenting practices applied by parents. The research subjects were selected using purposive sampling, consisting of parents who have children diagnosed with ADHD. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using an interactive analysis model including data reduction, data display, and conclusion drawing. The findings indicate that democratic parenting plays a significant role in enhancing the social well-being of children with ADHD. This parenting style is characterized by open communication, emotional support, consistent rules, and positive reinforcement. Children raised with this approach show improvements in communication skills, emotional regulation, and social adaptability. This study concludes that appropriate parenting not only functions as a caregiving process but also serves as an effective social support system in optimizing the social development of children with ADHD